ASUHAN IBU HAMIL SAMPAI DENGAN KB DAN NIFAS SECARA COC DI PMB YUNI WIDARYANTI, STr.Keb. Desa SUMBERMULYO JOGOROTO JOMBANG : SEBUAH TINJAUAN KASUS: A Midwifery Care Of Prenatal Up To Postnatal And Kb Of Coc In Obstetric Clinic Of Yuni Widaryanti, Str.Keb. At Sumbermulyo Village, Jogoroto District, Jombang Regency - Dian Puspita Yani (Jurnal Ilmiah Kebidanan (Scientific Journal of Midwifery), 2020)
The process of prenatal, childbirth and postnatal are stage of natural human reproduction, but it must be awared if something happens which can endager the health of mother and baby. The aim of this midwifery is to give midwefery care as continuity of care to Mrs M from the trimester III of prenatal to postnatal period and birth control (KB) program in obstetrics clinic of Yuni Windaryanti, STr. Keb at sumbermulyo village, Jombang regency in 2019. The method used in this case study uses qualitative research methods that are discrete with behaviors, perceptions, motivations, and actions using a case study design. This research has been carried out from 29 January 2019 until 20 April 2019, a purposive sampling sample. Data analysis was using descriptive analysis which was in accordance with midwifery care standards and progress notes with SOAP in PMB Yuni Windaryanti, STr.Keb Sumbermulyo village, Jombang district in 2019. The result of midwifery care has been done on Mrs M on the trimester III, Neonatal and postnatal are normal, the contraseption, which used injection every 3 months. It can be concluded that complaints and abnormalities that lead to pathological conditions inthe midwefery care from the trimester III up to KB program subjective and objective data are not not found. Then, there is No. urgent problems and the implementation is carried according to diagnosis. The suggestion to health workers are able to give midwifery care continuously.